Kritik Perspektif Karen Armstrong Terhadap Narasi Sirah Nabawiyah.docx - SAHNON, Syauqi Ahmad (Maliki Interdisciplinary Journal, 2024)
This article critically examines Karen Armstrong’s perspective on the narrative of Sirah Nabawiyah, focusing on the historical and analytical approach she employs in her work. Armstrong, known for her biography of Prophet Muhammad, seeks to blend theological sensitivity with historical analysis. This article explores how Armstrong highlights various aspects of the Prophet’s life, including the cultural and political challenges of his time, while critiquing traditional narratives that may be biased or lack contextual depth. The study also emphasizes Armstrong’s contribution in presenting Prophet Muhammad as a universal figure relevant to modern humanistic issues. Through a descriptive-analytical approach, this article aims to assess the accuracy, relevance, and implications of Armstrong’s critique of the Sirah Nabawiyah narrative in fostering a deeper understanding of Prophet Muhammad